The Volume of Federal Litigation and the Macroeconomy - Lance J. Bachmeier; Patrick Gaughman; Norman R. Swanson (Rutgers University, Department of Economics, 2003)
In this paper we examine the extent to which fluctuations in a number of macroeconomic variables impact on the volume of federal litigation cases. In particular, the impact of aggregate U.S. GDP, consumption, inflation, unemployment, and interest rates on the volume of antitrust, bankruptcy, contract, personal injury, and product liability cases between the years 1960 and 2000 is examined using Granger causal analysis and vector autoregression models (see e.g. Granger (1988)). Our empirical findings suggest that there are several linkages between macroeconomic variables and the volume of litigation cases, in broad agreement with the findings of Siegelman and Donohue (1995), who find that unemployment is an important determinant of the (number and) quality of employment cases filed. Most noteworthy, we find that there is a causal linkage from output, consumption and inflation to the total volume of federal litigation, so that predictions of future litigation volume can be improved by using information contained in current macroeconomic aggregates. Causation in the other direction (i.e. from the volume of litigation to macroeconomic activity) is not found in the data, however. Based on impulse response analysis, it is seen that shocks to income, consumption and inflation immediately lead to an increase in the volume of litigation, with shocks to inflation having the largest impact, and shocks to consumption having a rather moderate impact. In addition, the long run impact that shocks to each of these variables has on the volume of litigation is positive, regardless of whether the VAR or VEC model is used. Here, again, the impact of consumption is quite moderate, though. Additionally, similar results arise when examining the relation between various individual measures of federal litigation volume and the macroeconomy. Thus, the volume of federal litigation does not appear to be immune to the business cycle, a finding which is in broad agreement with the findings of Siegelman and Donohue.
Keywords: 330; Zivilprozess; Makroökonomischer Einfluss; Konjunktur; Kausalanalyse; Vereinigte Staaten